2018
DOI: 10.1016/j.bbrc.2017.11.171
|View full text |Cite
|
Sign up to set email alerts
|

Distorted antibody repertoire developed in the absence of pre-B cell receptor formation

Abstract: The pre-B cell receptor (pre-BCR), consisting of the μ heavy chain (μHC) and the surrogate light chain (SLC, Vpre-B and λ5), plays important roles during B cell development. The formation of the pre-BCR, which enables the nascent immunoglobulin HC to associate with the SLC, is considered a prerequisite for B cell development. However, a significant number of peripheral mature (leaky) B cells exist in SLC-deficient mice. These leaky B cells develop in the absence of pre-BCR and do not undergo the pre-BCR checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Nevertheless, the autoimmune reactions include spontaneous formation of T-cell dependent germinal centers, memory B cells and plasma cells that secrete autoantibodies, typical of those found in lupus (SLE), e.g., anti-DNA and anti-nuclear antibodies (ANAs) ( 94 , 95 ). Whether this is unique to mice lacking the entire SL chain is unclear, although splenic B cells in λ5T mice are also enriched for those expressing IgH chains with an arginine-rich H-CDR3 ( 98 ), and more recent work has shown that also λ5T mice secrete autoantibodies ( 90 ). In SLC −/− mice a subset of B cells resembles memory B cells expressing low levels of CD21 (CD21 −/low ) ( 99 ).…”
Section: A Role For the Pre-bcr In B Cell Tolerance?mentioning
confidence: 99%
“…Nevertheless, the autoimmune reactions include spontaneous formation of T-cell dependent germinal centers, memory B cells and plasma cells that secrete autoantibodies, typical of those found in lupus (SLE), e.g., anti-DNA and anti-nuclear antibodies (ANAs) ( 94 , 95 ). Whether this is unique to mice lacking the entire SL chain is unclear, although splenic B cells in λ5T mice are also enriched for those expressing IgH chains with an arginine-rich H-CDR3 ( 98 ), and more recent work has shown that also λ5T mice secrete autoantibodies ( 90 ). In SLC −/− mice a subset of B cells resembles memory B cells expressing low levels of CD21 (CD21 −/low ) ( 99 ).…”
Section: A Role For the Pre-bcr In B Cell Tolerance?mentioning
confidence: 99%
“…The URs are non-Ig domains of the two noncovalent bonded polypeptides, VpreB and λ5, which constitute the SLC [ 12 , 13 , 14 ]. The SLC is only expressed in a limited temporal stage of B cell development and may be involved in IgH allelic exclusion [ 15 ], downregulation of recombinant mechanisms [ 16 ], and functionally testing the μH chain, consequently shaping IgH repertoire [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly potent against invading pathogens due to its vast diversity, fine antigen recognition specificity, and the clonal expansion of antigen-specific B cells. The repertoire of antibody-producing B cells is estimated to be more than 10 15 in a single individual 1 . This immense diversity is generated with the help of VDJ gene recombination in the immunoglobulin genetic loci 2 .…”
Section: Introductionmentioning
confidence: 99%
“…. Interestingly, IGHV11-2 was also the most common major repertoire in our previously published analysis of naive IgM The method described here is useful for deciphering antigen-responsive antibody repertoires by inclusively analyzing the antibody-repertoire space generated in individual bodies, avoiding inadvertent omission of key antibody repertoires 8,10 . This method also allows the examination of detailed antibody network dynamism, which would facilitate accelerated discovery of protective antibodies against newly emerging pathogens.…”
mentioning
confidence: 96%
See 1 more Smart Citation